Glucagon-like peptide receptor agonists attenuate advanced glycation end products-induced inflammation in rat mesangial cells - Jui-Ting Chang; Yao-Jen Liang; Chia-Yu Hsu; Chao-Yi Chen; Po-Jung Chen; Yi-Feng Yang; Yen-Lin Chen; Dee Pei; Jin-Biou Chang; Jyh-Gang Leu (BMC, 2017)
Abstract Background Hyperglycemia-induced advanced glycation end products (AGEs) and receptor for AGEs (RAGE) production play major roles in progression of diabetic nephropathy. Anti-RAGE effect of peroxisome proliferator-activated receptor-delta (PPARδ) agonists was shown in previous studies. PPARδ agonists also stimulate glucagon-like peptide-1 (GLP-1) secretion from human intestinal cells. Methods In this study, the individual and synergic anti-inflammatory effects of GLP-1 receptor (exendin-4) and PPARδ (L-165,041) agonists in AGE-treated rat mesangial cells (RMC) were investigated. Results The results showed both exendin-4 and L-165,041 significantly attenuated AGE-induced IL-6 and TNF-α production, RAGE expression, and cell death in RMC. Similar anti-inflammatory potency was seen between 0.3 nM exendin-4 and 1 μM L-165,041. Synergic effect of exendin-4 and L-165,041 was shown in inhibiting cytokines production, but not in inhibiting RAGE expression or cell death. Conclusions These results suggest that both GLP-1 receptor and PPARδ agonists have anti-inflammatory effect on AGE-treated rat mesangial cells.